Sequenseoferuptionofcuspandbicuspmandibularteethinasampleof Peruvian children - Orellana Manrique, Tomás Oriel (2013)
It determine the sequense of eruption of permanent mandibular teeth, cusp, first bicusp and second bicusp, using a cross-sectional in a random sample of 67 child patients, 33 males and 34 females between 8 and 12 years old that where attended at Dentistry clinic of the Dentistry Faculty of the San Marcos Mayor National University between 2006 and 2011. For this study where used odontologic casts, pictures and panoramic radiographs of the patients. Relevant results where that for males and females, the sequence of eruption that predomine was 3, 4, 5